2004
DOI: 10.1111/j.1523-1739.2004.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Specimen Databases from Taxonomic Revisions for Estimating and Mapping the Global Species Diversity of Invertebrates and Repatriating Reliable Specimen Data

Abstract: We argue that the millions of specimen-label records published over the past decades in thousands of taxonomic revisions are a cost-effective source of information of critical importance for incorporating invertebrates into biodiversity research and conservation decisions. More specifically, we demonstrate for a specimen database assembled during a revision of the robber-fly genus Euscelidia (Asilidae, Diptera) how nonparametric species richness estimators (Chao1, incidence-based coverage estimator, second-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 36 publications
1
90
0
7
Order By: Relevance
“…) resulting in 12 samples. This approach was suggested by Meier & Dikow (2004) to use collection specimens for richness estimations, except that we used 10 year periods rather than 5 years because of the limited number of records for certain periods. As species richness is known to have a positive relationship with area size (Burgess et al 2004), this can be corrected for by using a mathematical approach using the formula developed by Rosenzweig (1995): BVd=BV/A z with BV being the biological value in question (in our analysis the species richness), A being the area (in square kilometers) and BVd the biological value corrected for area, and with z set at 0.2 as suggested by Burgess et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…) resulting in 12 samples. This approach was suggested by Meier & Dikow (2004) to use collection specimens for richness estimations, except that we used 10 year periods rather than 5 years because of the limited number of records for certain periods. As species richness is known to have a positive relationship with area size (Burgess et al 2004), this can be corrected for by using a mathematical approach using the formula developed by Rosenzweig (1995): BVd=BV/A z with BV being the biological value in question (in our analysis the species richness), A being the area (in square kilometers) and BVd the biological value corrected for area, and with z set at 0.2 as suggested by Burgess et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…To give an idea of the extent of the taxonomic literature which could be utilized for this purpose, a literature search by Meier and Dikow (2002) found that more than 2300 zoological revisions were published between 1990 and 2002. Given the success of the two attempts to utilize this information carried out so far, we believe that if this method is applied to a broader range of taxa, possibly incorporating additional explanatory variables, we will gain much insight into the magnitude and distribution of species richness which will help us focus taxonomic expertise and funding into areas where they are most needed.…”
Section: Discussionmentioning
confidence: 99%
“…Algunos beneficios del portal de GBIF son permitir el acceso a un alto núme-ro de registros y la repatriación de la información (Edwards, 2004). Sin embargo, pueden encontrarse diferentes problemas y errores en las bases de datos asociadas a GBIF (Meier & Dikow, 2004;Chapman, 2005;Yesson et al, 2007;Costello et al, 2012), algunos de estos son la presencia de sinonimias, errores tipográ-ficos y referencias geográficas incorrectamente relacionadas (Yesson et al, 2007;Costello et al, 2012). Así, una gran cantidad de datos disponibles en las bases de datos consultadas a través de la red, pueden no tener referencia geográfica o si la hay es imprecisa (Soberon & Peterson, 2009); en muchos casos, los registros representan a algunos taxones y se concentran en unas pocas regiones (Yesson et al, 2007).…”
unclassified